Management of acute appendicitis in an acute surgical unit: a cost analysis. Issue 12 (11th July 2018) - Wang, Edward; Jootun, Ravish; Foster, Amanda
Abstract : Background: The acute surgical unit (ASU) model of acute general surgery care offers efficient patient assessment, improved clinical outcomes and has been demonstrated to be cost‐efficient. Despite this, the management of acute appendicitis in our ASU was found to be highly cost‐negative. This study sought to identify the drivers of increased cost. Methods: A retrospective cost analysis of all patients with uncomplicated acute appendicitis in 2016 was undertaken to investigate the drivers of increased cost. The patient‐level costing approach was used to assign cost to patients. Results: The ASU management of uncomplicated appendicitis was found to have made a net loss of $625 000 in 2016. This study identified that the three largest cost drivers in appendicitis care were hospital overheads, bed day length of admission cost and operating theatre costs. Radiology, pathology and pharmacy costs did not affect total cost significantly. Conclusion: Two key targets for improvement were identified. First, reduced theatre turnaround times will allow more efficient theatre utilization. Second, improved after‐hours and weekend theatre availability will reduce preoperative waiting time‐related cost.